The Aspects of Educational Globalization in the Context of System Globalization - MYKHAYLYSHYN, GALYNA; KONDUR, OKSANA (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2018)
The article is devoted to the study of the processes in the modern world educational system in the conditions of globalization. An effort of systematically analysis of the characteristics of the institutional dimension of internationalization and transformation of the educational system in a globalized world. It is proposed to use globalization and the informational and technological revolution to rebuild education in the direction of its democratization and progressive social changes radically. In order to solve these problems there exist a necessity in the education to be-come a social institution in the interests of the social majority, as it proposed by representatives of modern pedagogy.